CULTIVATING CULTURAL INTELLIGENCE: AN IN-DEPTH ANALYSIS OF THE INTERPLAY BETWEEN CULTURAL INTELLIGENCE, SECOND LANGUAGE MOTIVATION, AND SOCIOLINGUISTIC COMPETENCE AMONG TURKIC LANGUAGE SPEAKERS IN AUSTRALIA - Gavhar Khamidovna Abdullaeva (Western European Studies, 2024)
This study explores the relationships between cultural intelligence, second language motivation, and sociolinguistic competence among Turkic language speakers in Australia. The research aims to investigate how cultural intelligence influences language motivation and the development of sociolinguistic competence. Employing a mixed-methods approach, this research combines quantitative surveys and qualitative discourse analysis to contribute new insights into intercultural communication and language education in multicultural settings.
Keywords: Cultural Intelligence; Second Language Motivation; Sociolinguistic Competence